Buzzati and Nabokov: It is not about desire. (November 2022) - Castelli, Alberto
Dino Buzzati's Un Amore has been largely defined as a consequence of the progressive development of the phenomenon of "lolitism, " and a few years before, Nabokov's Lolita had been accused of being an example of pedophilia. While both female characters are archetypes of "nymphet, " defiant, sexually promiscuous, capricious, and, above all, skilled in manipulation, the relationship progresses through a labyrinth of absence and deprivation. However, in order to place the novels in a proper perspective, we must avoid any intrusion into the authors' private sexuality, and search for the aesthetic phenomenon thereby implied. Written from the male's perspective, women are a riddle but their age offers a key to understanding: youth's artful image can grant the illusion of immortality before death.